(untitled) (Research, Society and Development, 2022)
This discussion, based on a literature review, aims to reflect on the importance that studies on Critical Mathematics Education (CME) be inserted, in a practical-pedagogical way, in the curriculum of degree courses in mathematics. Brazil is in the last positions in the PISA ranking, which is a test that evaluates the student beyond the reproduction and memorization of mathematical concepts. In this sense, we believe that working on concepts and practices involving CME during the degree in mathematics can be one of the alternatives to achieve better results in the medium/long term in these assessments, adding training knowledge to future teachers. In addition, the main focus is that these teachers can contribute to the integral development of students so that they are not just recipients of content, but can in fact obtain adequate proficiency in mathematics that allows them to critically read the context in which they are inserted, acting about it.